Anaplasma marginale modulates the microbiota of Rhipicephalus microplus organs involved in pathogen transmission - Pérez, Agustina Ericlee; Guillemi, Eliana Carolina; Abuin-Denis, Lianet; Piloto-Sardiñas, Elianne; Obregón, Dasiel; Pin Viso, Natalia Daniela; Sarmiento, Nestor Fabian; Cabezas-Cruz, Alejandro; Farber, Marisa Diana (Elsevier, 2025)
The cattle tick Rhipicephalus microplus is a vector for Anaplasma marginale in tropical and subtropical regions worldwide. The study of pathogen-microbiome-vector interactions at the tick organ scale is a promising area of development, unraveling control strategies for tick-borne diseases. Our study focused on how A. marginale infection affects the bacterial community within the salivary glands and ovaries of R. microplus. Engorged female ticks collected from cattle in a disease-endemic area of Argentina were further classified based on whether they were infected with A. marginale by targeting the msp1β gene through PCR diagnosis in tissue samples. We included negative control samples throughout the study. We analyzed the bacterial communities in tick tissues by sequencing the 16S rRNA V3-V4 region. Our results revealed significant differences in community composition between infected and uninfected samples. Sphingomonadaceae was identified as a predominant taxon in uninfected salivary glands and ovaries. Additionally, we constructed co-occurrence networks to study interactions within the microbial communities. It is noteworthy that A. marginale infection led to an increase in network complexity in the salivary glands, exerting the opposite effect on the ovaries. These findings reinforced the hypothesis that A. marginale impacts the microbiota of R. microplus at an organ-specific level.